Growth and Welfare Effects of Education: Evidence from Asian Countries - Abubakar, Attahir Babaji; Addi, Haman Mahamat; Bala, Ahmed Jinjiri (Panoeconomicus, 2024)
Considering the potential role of education in enhancing the socioeconomic prosperity of countries, this study examines the effect of education on economic growth and household welfare in Asian countries. Static and dynamic panel data estimation techniques were employed for analysis. The findings of the study reveal a significant positive effect of education on economic growth and household welfare, with the growth effect of male education being marginally higher than female education. Interestingly, the household welfare effect of female education is revealed to be higher than male education. These findings imply that for economic growth and household welfare enhancement in the region, female education is as important as male education. Consequent to these findings, the study emphasises the need for policy measures aimed at enhancing both access and quality of education for people of all genders in the region. JEL: I25, J24